1985
DOI: 10.1111/j.1399-0004.1985.tb00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of X‐linked hypohidrotic ectodermal dysplasia in six males and in their mothers

Abstract: Six male patients with confirmed X-linked hypohidrotic ectodermal dysplasia and their mothers were studied to determine the variation of expressivity in patients and heterozygotes, major problems of the patients, and to find a clue to pathogenesis.The number of teeth, conic in shape, in patients varied from none to 14. In addition to hypohidrosis and hypotrichosis, dry skin, reduced salivation, hoarseness and hypoplasia of the nipples were common signs. Five patients had frequent respiratory infections.The mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The significantly reduced saliva flow rate found both in the affected males and the female carriers is in agreement with the findings of previous studies of persons affected by ectodermal dysplasia 7–10 . Among the female carriers, the reduction in saliva flow rate seemed to be independent of their number of missing teeth.…”
Section: Discussionsupporting
confidence: 91%
“…The significantly reduced saliva flow rate found both in the affected males and the female carriers is in agreement with the findings of previous studies of persons affected by ectodermal dysplasia 7–10 . Among the female carriers, the reduction in saliva flow rate seemed to be independent of their number of missing teeth.…”
Section: Discussionsupporting
confidence: 91%
“…In the case of XLHED‐affected registrants, findings from the Registry analysis update and extend the data from prior, smaller datasets [Soderholm and Kaitila, ; Clarke et al, ; Clarke et al, ] and thus reaffirm key medical issues including: (1) significant infant/childhood mortality; (2) nutritional and growth challenges; (3) lifelong nasal/respiratory problems in both male and females affected by XLHED; and (4) dental interventions (and associated costs) that continue to be a common and significant health issue for XLHED patients. Physical and historical findings that differ between XLHED and other ED syndromes will facilitate their differential diagnosis.…”
Section: Discussionmentioning
confidence: 54%
“…Reviews of the spectrum of clinical issues in XLHED [Soderholm and Kaitila, ; Clarke et al, ] reported a number of less common but medically significant complications that impact the quality of life in individuals affected by this disorder. These are confirmed and extended in the Registry data.…”
Section: Resultsmentioning
confidence: 99%
“…X-linked hypohidrotic ectodermal dysplasia (XLHED) is a hereditary defect that causes malformations of structures that emerge from the ectoderm, including hair, teeth and sweat glands (Söderholm and Kaitila 1985; Clarke 1987; Kere et al 1996; Itin 2014). XLHED manifests in humans with alopecia, a lack of sweat glands and possibly other exocrine glands, oligodontia and conically shaped teeth (Clarke et al 1987; Cluzeau et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The affected individuals therefore suffer from hypohidrosis, which can lead to hyperthermia (Mills 1968). They are also affected with decreased mucociliary clearance, predisposing to respiratory tract infections, decreased lacrimal function and dry eye, and problems with mastication (Beahrs et al 1971; Söderholm and Kaitila 1985; Clarke et al 1987; Gilgenkrantz et al 1989; Johnson et al 2002; Casal et al 2007). In humans, XLHED is the most frequent form of ectodermal dysplasias (Kere et al 1996).…”
Section: Introductionmentioning
confidence: 99%